2016
DOI: 10.1136/tobaccocontrol-2016-053088
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence attitude and enforcement of the smoke-free law in Turkey: a survey of hospitality venue owners and employees

Abstract: Although the attitude towards the law was positive, interventions are needed to increase knowledge on the health effects of SHS and facilitate enforcement of the law, particularly among subgroups less likely to have a positive attitude and enforce the law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Our study has shown that only 28.3% of respondents cautioning the others to stop smoking in smoke-free areas, which also means that more than 70% of respondents are tolerant to tobacco smoke in smoke-free areas. This result is similar to a study among hospitality venue owners and employees in 7 cities of Turkey where 71.3% of participants displayed a positive attitude towards the smoke-free law, but only 19.5% of participants reported requesting customers or employees to stop smoking in the venues [ 27 ]. The practice of intervening a smoker who is both smoking and violating smoke-free regulations plays an important role in tobacco control for several reasons.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our study has shown that only 28.3% of respondents cautioning the others to stop smoking in smoke-free areas, which also means that more than 70% of respondents are tolerant to tobacco smoke in smoke-free areas. This result is similar to a study among hospitality venue owners and employees in 7 cities of Turkey where 71.3% of participants displayed a positive attitude towards the smoke-free law, but only 19.5% of participants reported requesting customers or employees to stop smoking in the venues [ 27 ]. The practice of intervening a smoker who is both smoking and violating smoke-free regulations plays an important role in tobacco control for several reasons.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, a study by the Ministry of Health of Vietnam et al in 2010 [ 19 ] also reported that the higher proportion of supporting for smoke-free law fell on the group of the older age, married and higher educational attainment. The reason is that these people are more knowledgeable about the health effects of secondhand smoke and show more positive attitudes towards smoke-free law [ 27 , 29 ]. Interestingly, we found that people with lower economic status such as in the second and middle quintile were more likely to request smokers to stop smoking than those in the fourth and richest quintile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the included articles were selected for meeting the criteria of discussing problems faced or lessons learned. Additionally, we incorporated relevant findings from our own work on smoke-free policies in South-East Asia 22,23 , Africa 24,25 , and globally 26-30 . We focus on post-legislation implementation — which we define as putting a smoke-free policy into practice and enforcing it to achieve the public’s compliance with the policy.…”
Section: Methodsmentioning
confidence: 99%
“…Sociodemographic analysis showed that only the education level of the respondents significantly affected the compliance in worship places. The effect of education level on compliance with SFL is not only found in developing countries, but also in developed countries which have implemented SFL with many approaches (Aherrera et al, 2017). The education level of respondent in our study showed that most of them has passed high school and undergraduate degree.…”
Section: Discussionmentioning
confidence: 53%